Cheer up! : love and pompoms - Frasier, Crystal (Oni Press, 2021)
"Annie is a smart, antisocial lesbian starting her senior year of high school who's under pressure to join the cheerleader squad to make friends and round out her college applications. Her former friend BeBe is a people-pleaser, a trans girl who must keep her parents happy with her grades and social life in order to maintain their support of her transition. Through the rigors of squad training and amped up social pressures (not to mention micro-aggressions and other queer youth problems), the two girls rekindle a friendship they thought they'd lost and discover there may be other, sweeter feelings springing up between them."--Back cover.